The Handbook of Scholarly Writing and Publishing - Krishna Bista (Journal of MultiDisciplinary Evaluation)
A review of the book The Handbook of Scholarly Writing and Publishing edited by Tonette S. Rocco and Timothy Gary Hatcher with a forward written by John W. Creswell, published in 2011 by Jossey-Bass.